2002
DOI: 10.1038/sj.bjc.6600075
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of matched preoperative plasma and serum VEGF in patients with primary colorectal carcinoma

Abstract: In serum, the major part of vascular endothelial growth factor derives from in vitro degranulation of granulocytes and platelets. Therefore, plasma may be preferred for vascular endothelial growth factor measurements. However, which specimen is the best predictor of survival is still debated. The present study analyzed the prognostic value of matched preoperative serum and plasma vascular endothelial growth factor concentrations in patients with colorectal cancer. To establish the reference range among healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
67
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 9 publications
(14 reference statements)
6
67
0
2
Order By: Relevance
“…As most serum VEGF is released from platelets during blood clotting, it has been suggested that plasma VEGF may be a better reflection of ongoing angiogenic activity, although this assumption has been challenged (Banks et al, 1998;Salven et al, 1999a;Wynendaele et al, 1999;George et al, 2000). To date, plasma VEGF has not been shown to be a better prognostic factor than serum VEGF in any solid tumour (Werther et al, 2002).…”
mentioning
confidence: 97%
“…As most serum VEGF is released from platelets during blood clotting, it has been suggested that plasma VEGF may be a better reflection of ongoing angiogenic activity, although this assumption has been challenged (Banks et al, 1998;Salven et al, 1999a;Wynendaele et al, 1999;George et al, 2000). To date, plasma VEGF has not been shown to be a better prognostic factor than serum VEGF in any solid tumour (Werther et al, 2002).…”
mentioning
confidence: 97%
“…Correspondingly, palliatively treated dogs (group B) with a low plasma VEGF level that responded to therapy had also a significantly longer TTF and a longer live span. In a human colorectal cancer study, it was also shown that high plasma and serum VEGF concentration prior to surgery predicted decreased overall survival [5,29].…”
Section: Discussionmentioning
confidence: 99%
“…When serum and plasma VEGF in patients with primary colorectal carcinoma were analyzed separately, both, high serum and high plasma VEGF concentrations predicted for shorter survival, but significance was only reached for serum VEGF values [29]. In contrast, high plasma VEGF was shown to be a significant predictor of reduced overall survival and of earlier onset of local recurrence for patients with breast cancer [23,30].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In February 2002, we published an article in the Br J Cancer concerning the prognostic impact of matched preoperative plasma and serum VEGF in patients with primary colorectal carcinoma (Werther et al, 2002).…”
Section: Sirmentioning
confidence: 99%